Geoquímica e proveniência dos sedimentos da formação corumbataí na região de Rio Claro/SP - Zanardo, Antenor [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Montibeller, Cibele Carolina; Rocha, Rogers Raphael da; Moreno, Maria Margarita Torres [UNESP]; Del Roveri, Carolina; Azzi, Andrezza de Almeida (My University, 2017)
Corumbataí Formation in Rio Claro – Limeira – Araras (São Paulo State, Brazil) is represented by a succession of siltstones mainly consisting of phyllosilicates (predominating illite, although montmorillonite, biotite, chlorite, kaolinite and mixed-layer clay minerals are also present), quartz, feldspars, carbonates, hematite, goethite and zeolites, which may be of authigenic and/or detrital origin. Chemically the rocks of Corumbataí Formation are mainly classified as wackes and secondarily as shales, whose main source are felsic igneous rocks and/ or quartzose sedimentary rocks. The application of chemical maturity indexes in the analyzed rocks suggests that these are chemically immature and that the source was subjected to conditions of moderate weathering. Discriminant diagrams for tectonic environments suggest that the source of the Corumbataí Formation sediments are chemically similar to rocks formed in active margin and/or island arcs, although deposited in another geotectonic setting (intracratonic basin).
Keywords: Corumbataí formation; Geochemistry; Paraná basin; Permian